Effects of different nutrient solutions on the acclimatisation of in vitro Caladium plantlets using a simplified hydroponic system - Zhang, Yuan-Shan; Gu, Si-Jia; Chen, Jin-Jin; Cai, Xiao-Dong (Penerbit Universiti Kebangsaan Malaysia, 2019)
An efficient acclimatisation protocol is critical to improve the survival rate and promote growth of in vitro plantlets. Herein, tissue-cultured plantlets of ‘Red Flash’ caladium (Caladium × hortulanum Birdsey) were treated with deionised water and three nutrient solutions including Japanese garden formula (JG), South China Agriculture University formula B for leafy vegetables (SCAU-B) and Hoagland solution in a simplified hydroponic system under indoor environmental conditions. The results showed that all the plantlets survived after 30 days of hydroponic culture, and the three nutrient solutions showed significant positive effects on the plant growth and the content of chlorophyll a, chlorophyll b, total chlorophyll, carotenoid, soluble sugar and soluble protein compared to the deionised water treatment. No significant difference was recorded for the other growth parameters except the average leaf number per plantlet among the nutrient solution treatments. For the analysed physiological parameters, the plantlets treated by SCAU-B contained significantly higher content than those of the Hoagland treatment except the protein content. No significant difference was found between the JG and the SCAU-B treatment except the carotenoid content, and between the JG and the Hoagland treatment except the protein content. The plantlets acclimatised in the nutrient solutions also had a good performance when transferred to plastic pots. These results implied that water alone was not capable of maintaining healthy growth of in vitro caladium plantlets, and hydroponics approach using the three nutrient solutions could be a feasible method for acclimatisation of the plantlets.